Periodontal disease as a Risk Indicator of Cardiovascular Disease: A Clinicobiochemical study - Gautam, Abhishek; Shekhar, Saurabh; Kumari, Shiprita; Upasana, Kumari; Raina, Sakshi (Journal of Neonatal Surgery, 2025)
Purpose: To determine whether patients with chronic periodontitis have higher plasma concentrations of risk markers for atherosclerosis. Materials and Methods: A randomized, controlled study was conducted on 17 patients suffering from chronic generalized periodontitis and 17 healthy individuals. Each patient underwent comprehensive periodontal examination and haematological evaluation, recorded at baseline. Results: The groups were matched age, sex and physical built wise and no significant difference in the BMI of two groups (p=0.354) could be seen. Lipid profile in study group (4.4±0.5) was significantly higher statistically (p<0.001) as compared to the control group (3.3±0.5). Mean C-reactive protein (CRP), was found to be 4.7±2.3 mg/lt in the study group and 2.4±1.6 mg/lt in the control group, showing a significant difference statistically (p=0.002). Conclusion: Periodontal status was the only differentiating factor between the two group and the cardiovascular risk factors (like CRP) were more pronounced in the severe periodontitis group, indicating that the risk of cardiovascular disease is significantly higher in these patients.